Public Management in local government units in the example of the municipality of Mstów - Kabus, Judyta; Kańa, Radomir; Nowakowska-Grunt, Joanna (International Journal of Engineering and Technology, 2018)
Today’s units of local government is identified not only with the power that is necessary for the realization of public tasks but above all, it is accentuated by the importance of meeting the needs which are important from the point of view of the community, including the Management processes.The purpose of this work is to present a smooth and effective public management process carried out by the municipal government of Mstów. This municipality applies practical New Public Management instruments in building and implementing the regional development strategy. The article was prepared on the canvas of literature studies on the management, organization, and planning of universal services of a public interest and analysis of the statistical data collected by the municipality.